Acrylamide exposure, sex hormones, and pubertal status in Japanese adolescents. - Nagata, Chisato; Wada, Keiko; Yamakawa, Michiyo; Sugino, Masaaki; Mori, Tomoka; Ueyama, Jun; Sumoto, Yoshio (International Journal of Environmental Health Research, 2025)
Acrylamide may affect sex hormone levels and the timing of sexual maturation. The present study cross-sectionally examined interrelationship between the urinary metabolite of acrylamide exposure, serum sex hormone levels, and pubertal status in 408 Japanese adolescents aged 13–14 years. Their caregivers completed a questionnaire concerning the health status of their children, including pubertal maturation, and the lifestyles of children and parents. Pubertal status was queried by the Pubertal Development Scale. A major metabolite of acrylamide, N-acetyl-S-(2-carbamoylethyl)-cysteine (AAMA) in first-void urine samples. In male students, urinary AAMA was significantly inversely associated with testosterone, puberty stage, and facial hair growth after controlling for covariates. Serum testosterone and DHEAS were significantly positively associated with puberty stage. In female students, urinary AAMA was not associated with puberty stage, the indices, or any measured hormones. The data suggest that exposure to acrylamide may impact the pubertal development of boys through the effects on testosterone level.